Vehicle-Tracking Mobile Application without a GPS Sensor - Priyaporn Ratsame; Mojira Koedsaksit; Sompatthana Jitsoontron; Unchasa Jaisamak; Supachai Puengsungewan (Indonesian Journal of Educational Research and Technology, 2021)
A GPS sensor is the main part of the system in vehicle tracking applications. However, a GPS sensor becomes the limitation of low-cost vehicle tracking applications because a GPS sensor comes with the running cost of our vehicle tracking system. To solve this problem, this paper presents an IoT based concept to track a vehicle without a GPS sensor. To evaluate the proposed concepts, a light sensor and a vibration sensor have been compared to show the real-time data. The proposed algorithm shows that the vibration sensor provides a high accuracy more than a light sensor.